The Chemical Composition of Soyhulls and Their Effect on Amino Acid and Nutrient Digestibility in Laying Hens during the Peak of Production - Muhammad Shuaib; Deependra Paneru; Abdul Hafeez; Muhammad Tahir; Woo Kyun Kim (Animals, 2023)
This study investigates the chemical composition of soyhulls (SHs) as an alternative feed ingredient and their effect on nutrient and amino acid (AA) digestibility in laying hens during peak production. A total of 200 golden brown hens (28 weeks old) were subjected to random allocation across 5 dietary treatments: a corn–soybean meal (SBM) reference diet and 4 test diets with 25% SHs from different mills (SH1, SH2, SH3, and SH4). Each treatment was replicated four times with ten birds per replicate. Digesta samples were collected during three phases (28–32, 32–36, and 36–40 weeks of age) to measure apparent metabolizable energy (AME), the apparent ileal digestibility (AID) of nutrients, and the standard ileal digestibility (SID) of AAs. The SBM diet had 30.0% crude protein (CP) and 3.78% crude fiber (CF), while the SH diets had 21.0 to 21.5% CP and 11.6% CF. The findings revealed that the AME was lower (p < 0.05) with SH diets (2404 kcal/kg) compared to the SBM diet (2627 kcal/kg) in all three phases. The SH diets had a lower AID of dry matter (DM), crude protein (CP), ash, ether extract (EE), and crude fiber (CF) than the SBM diet by an average of 2.88, 2.25, 4.93, 4.99, and 3.36%, respectively. The AID of nitrogen-free extract (NFE) was higher in the SH diets than the SBM diet by 3.42% in all three phases (p < 0.05). The SH diets had lower uric acid excretion (about 66.93 mg/100 mL) than the SBM diet (about 76.43 mg/100 mL) on average in all three phases. The SH diets had a lower SID of arginine, histidine, isoleucine, lysine, cysteine, valine, and tyrosine than the SBM diet by 2 to 10%, while the SID of methionine was higher in the SH diets than the SBM diet by 2.2% on average in all three phases (p < 0.05). The SH from Sadiq Brother Feed (SH1) had the highest AME and AID of DM, ash, CP, EE, CF, and the SID of AA among the SH diets. These results indicate that SH can partially replace SBM in laying hen diets, but the source and quality of SH should be considered.